2016
DOI: 10.22323/2.15050204
|View full text |Cite
|
Sign up to set email alerts
|

Using social network analysis to document science festival partnerships

Abstract: This study applies social network analysis to explore the role that one science festival has played in building the state's STEM learning ecosystem. It examines the breadth and extent of collaboration among STEM educators and their partners, reviewing past and present partnerships across 449 events during the 2015 festival. Three case studies provide in-depth illustrations of partnerships. These findings represent an important step towards (a) mapping a STEM learning ecosystem, and (b) trying to understand how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Academic research in this area has been sparse [Bultitude, 2014] and of variable quality [Jensen and Buckley, 2014]; however in recent years the literature has started to expand [e.g. Fogg-Rogers et al, 2015;Peterman and Young, 2015;Bevc, Young and Peterman, 2016;Kennedy, Jensen and Verbeke, 2017;Rose et al, 2017;Canovan and Luck, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Academic research in this area has been sparse [Bultitude, 2014] and of variable quality [Jensen and Buckley, 2014]; however in recent years the literature has started to expand [e.g. Fogg-Rogers et al, 2015;Peterman and Young, 2015;Bevc, Young and Peterman, 2016;Kennedy, Jensen and Verbeke, 2017;Rose et al, 2017;Canovan and Luck, 2018].…”
Section: Introductionmentioning
confidence: 99%
“…Adhikari et al [2019], for example, analyzed the impacts of the Pint of Science Festival in Thailand -a six-day effort which featured interactive talks that were 12-20 minutes in length and were designed to elicit public discussions of science content. Bevc, Young and Peterman [2016], on the other hand, focused on the North Carolina Science Festival -a month-long festival that featured events in a variety of formats (e.g. a large-scale expo, sky watching sessions, technology demonstrations, science shows, competitions).…”
Section: How Science Festivals Are Described In the Literaturementioning
confidence: 99%
“…In their efforts to engage tens of thousands of visitors across the country every year, members of the broader science festival community rely heavily on collaborations between informal science institutions, universities, businesses, community groups, and other STEM organizations [Wiehe, 2014;Science Festival Alliance, 2018]. A social network analysis of the North Carolina Science Festival demonstrated how this annual celebration plays a critical role in strengthening the state's STEM learning environment and infrastructure by bringing events to new communities and building relationships between cooperating groups that persist well after the festival itself has ended [Bevc, Young and Peterman, 2016]. A similar social network analysis of the Edinburgh Science Festival revealed the complex and interdependent nature of those who staff and organize such efforts [Jarman, 2016].…”
Section: Finding Common Ground: Expected Outcomes For Science Festival Visitorsmentioning
confidence: 99%
“…The gaps identified by CAISE reiterate the need for scholarship in this area. As noted earlier, we are aware of only one study that has investigated the contributions that festivals make to the larger, local informal learning network (Bevc et al, 2016). Little is known about the ways that festivals are situated within their local STEM learning landscape, or the unique and supportive contributions they might make as an informal learning mechanism within that landscape.…”
Section: Integrating Systems Perspectives and Studying Inclusive Prac...mentioning
confidence: 99%
“…A final example from the literature focused on the contributions that festivals make to the local STEM learning ecosystem. In the only study found to date that does not focus on visitors, at least in part, Bevc et al (2016), found that a science festival was an effective mechanism for fostering new partnerships between informal learning institutions. By gathering retrospective data before the festival and data on partnerships after the festival, this study demonstrated that partnerships were sustained both within and outside the festival context.…”
Section: Introductionmentioning
confidence: 99%